Involvement of PtPHR1 in phosphates starvation-induced alkaloid biosynthesis in Pinellia ternata (Thunb.) Breit - Wang, Huihui; Hu, Jitao; Li, Linying; Zhang, Xueying; Zhang, Hao; Liang, Zongsuo; Sheng, Qing; He, Yuqing; Hong, Gaojie (Frontiers in Plant Science, 2022)
Nowadays, because of the great benefit to human health, more and more efforts have been made to increase the production of alkaloids in Pinellia ternata (Thunb.) Breit. Phosphate (Pi) plays a critical role in plant growth and development, as well as secondary metabolism. However, its effect and regulation mechanism of Pi signaling on alkaloid biosynthesis calls for further uncovered. Here, we reported that Pi starvation could induce alkaloid accumulation in P. ternata. We cloned a cDNA sequence encoding PtPHR1 from P. ternata, which was further identified by nuclear localization, transcription activity and binding ability to the PHR1-binding sequence. We found that transformation of PtPHR1 into the Arabidopsis phr1 mutant (designated as PtPHR1OE/phr1) led to the rescue of the phenotype of the phr1 mutant to that of wild-type, including the expression level of Pi starvation-induced genes and anthocyanin accumulation. The combination of these biochemical and genetic experiments indicated that PtPHR1 was intended to have a role similar to that of AtPHR1 in Pi signaling and metabolic responses. Interestingly, we found that Pi starvation also induced the production of benzoic acid, an intermediate in the biosynthetic pathway of phenylpropylamino alkaloids. Furthermore, this induction effect was impaired in the phr1 mutant but partly recovered in PtPHR1OE/phr1 plants. Together, our data suggests that Pi starvation promoted benzoic acid -derived alkaloid biosynthesis in P. ternata was under control of PtPHR1. Our finding that PtPHR1 is involved in the regulation of Pi signaling on alkaloid biosynthesis shows a direct link between the Pi nutrient supply and secondary metabolism.